The new Koreans the story of a nation - Breen, Michael 1952- (Thomas Dunne Books/St. Martin's Press, 2017)
"Just a few decades ago, the Koreans were an impoverished, agricultural people. In one generation they moved from the fields to Silicon Valley. The nature and values of the Korean people provide the background for a more detailed examination of the complex history of the country, in particular its division and its emergence as an economic superpower. Who are these people? And where does their future lie? In this absorbing and enlightening account, Michael Breen provides compelling insight into the history and character of this fascinating nation "--